(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
When lockdown started, I moved to working remotely, engaging in online therapy with patients from a room in my house. There were many challenges to the frame of therapy. As lockdown continued, I found myself defending the ideals and value of The Frame and becoming angrier with each perceived attack. Many colleagues, friends and patients saw the change to online work an opportunity. Throughout life, we all embody and are embodied by a frame. This paper, based upon my presentation, is an attempt to examine the role and meaning of existentially understood frames in being-with the challenges of trauma.